PENGARUH PENERAPAN STRATEGI QUESTIONS STUDENTS HAVE TERHADAP PEMAHAMANKONSEP MATEMATIS SISWA KELAS VIII SMP MUHAMMADIYAH 6 PADANG - Bisefni, Elwing; Rismen, Sefna; Zulfaneti, Zulfaneti (Pendidikan Matematika, 2013)
The research was background by matematics concept comprehension class VIII SMP Muhammadiyah 6 Padang is still lacking. The purpose of this study to determine whether students matematics concept comprehension by Questions Students Have Applying strategy better than the students matematics concept comprehension by applying conventional learning. This type of research is experimental research. The study population was all eighth grade students enrolled Muhammadiyah 6 Padang school year 2012/2013. Sampling technique is random. The instrument used in this study is to test the indicators of matematics concept comprehenson, a test that is used is a form of essay with a reliability test is Â Â 0.86. Techniques of data analysis using t-test of the party. Based on the obtained hypothesis test thitung = 2, 75 > ttabel = 1, 67, then the hypothetical in this study received. It can be concluded that the students matematics concept comprehension that apply Questions Students Have beter than the students matematic concept comprehension using conventional learning.